EFFECTS OF CLASS SIZE ON STUDENTS’ ATTITUDE AND ACADEMIC PERFORMANCE IN ENGLISH LANGUAGE AMONG SECONDARY SCHOOL STUDENTS IN ADO LOCAL GOVERNMENT, EKITI STATE - Olurotimi, Babalola Joseph; Nike, Awe Olasunbon (LLT Journal: A Journal on Language and Language Teaching, 2021)
The need to get every individual educated in Nigeria necessitated the introduction of education policies like the Universal Primary Education, UPE (1976) and the Universal Basic Education, UBE (1999). The resultant effect of these policies is a steady and constant increase in schools’ enrolment, especially at the primary and secondary school levels. This led to overpopulation in the schools with some classes having as many as sixty students and sometimes above in a single arm. This study, through the analysis of questionnaires administered to students and their teachers, as well as the analysis of the examination results of selected students in JSS2 class looks at the effects of class size on students’ attitude and academic performance in the English language. The result of the analysis confirms a negative effect of large class size on the attitude and academic performance of students in the English language while the effect of small class size is positive on the students’ attitude to the learning of English language and consequently on their academic performance. As a corollary, the study establishes that teachers’ productivity is more positively enhanced in small classes than in large classes. On the basis of the findings, appropriate recommendations are made to ameliorate these negative effects and to reduce the incidence of large class size in our secondary schools in Ekiti State, Nigeria.